Rancang Bangun Smart Door Access Berbasis Fingerprint untuk Keamanan Ruang Laboratorium - Zeluyvenca Avista; Oldy Fahlovi (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Laboratory space is a place to store important assets, so security is an important factor. The application of technology is needed to help security in the laboratory space. In addition, with various technology options, it is necessary to consider human errors that often occur. The use of smart door access with a mechanism using a fingerprint sensor is determined due to security considerations and minimizing human error. Security is guaranteed because only registered fingerprints can access the room. The microcontroller uses Arduino Uno as a system driver that has been programmed in the Arduino IDE. The system works according to the function where the outer door uses a fingerprint sensor while the inner door uses a touch sensor to move the solenoid door lock. Three variations were carried out, namely clean fingers, dusty fingers and wet fingers to observe fingerprint performance. The fingerprint sensor works quickly when the finger is clean then the finger is wet and finally the finger is dusty. The length of time the solenoid door lock opens when the smart door access system is operated according to the settings in the Arduino IDE program.